(untitled) (Acta Scientiarum. Technology, 2011)
Biochemical analyses are important tools for discovering new bioactive compounds for medical clinic. This study aimed at isolating iota-carrageenans (Î¹-CARs) from Solieria filiformis (Rhodophyta) by enzymatic extraction (EE), refined hot-water extraction (RHWE) and hot-water extraction (HWE), and test (EE, s.c.) their anti-inflammatory effects in the peritonitis model using the Lambda-carrageenan (700 Âµg cavity-1, i.p.) as an inflammatory stimuli in rats. The activated partial thromboplastin time (APTT) was also evaluated in Î¹-CARs fractions, obtained by ion-exchange chromatography (DEAE-cellulose), using rabbit plasma and compared to heparin (193 IU mg-1). The results showed that the Î¹-CARs (EE) (3 or 9 mg kg-1) containing 89.92% total sugars, 29.02% sulfate and absence of contaminant proteins inhibited (p < 0.05) the cellular infiltrate in the peritoneal cavity of the animals, but with 27 mg kg-1 had no anti-inflammatory effect (p > 0.05). Similar chromatography profiles were obtained among the methods; however, with fractions revealing different pattern on charge density by electrophoresis. Fractions had no virtually effects on APTT (1.16, 1.73 and 1.59 IU mg-1 for EE, RHWE and HWE, respectively). Further investigations to better understanding the actions of S. filiformis Î¹-CARs (EE) in the inflammatory response are suggested.